KESELARASAN ANTARA SYARIAH DAN FALSAFAH (Studi Pemikiran Ibn Rusyd dalam Kitab Fasl al-Maqal) - Muhammad Tamtowi (Universitas Islam Negeri Ar-Raniry, 2011)
Reason and revelation dichotomy has strengthened the stigma of Islamic thoughts. The use of reason is often suspected as a source of error. Philosophy as a method of rational thinking as the problem accused of infidelity. Ibn Rushd participated in the arena of scientific debate with the brilliant idea of harmonizing between shari’ah and philosophy. For Ibn Rushd, the shari’ah and philosophy are not mutually contradictory. Instead, they are best friends which reinforce each other and strengthen the Islamic Pillars.